Canine Adenovirus 1 Isolation Bioinformatics Analysis of the Fiber - Wang, Ben; Wang, Minchun; Zhang, Hongling; Xu, Jinfeng; Hou, Jinyu; Zhu, Yanzhu (Frontiers in Cellular and Infection Microbiology, 2022)
Canine adenovirus type 1 (CAdV-1) is a double-stranded DNA virus, which is the causative agent of fox encephalitis. The Fiber protein is one of the structural proteins in CAdV-1, which mediates virion binding to the coxsackievirus and adenovirus receptor on host cells. The suspected virus was cultured in the MDCK cells, and it was determined through the cytopathic effects, sequencing and electron microscopy. The informatics analysis of the Fiber was done using online bioinformatics servers. The CAdV-1-JL2021 strain was isolated successfully, and were most similar to the CAdV-1 strain circulating in Italy. The occurrence of negative selection and recombination were found in the CAdV-1-JL2021 and CAdV-2-AC_000020.1. Host cell membrane was its subcellular localization. The CAdV-1-JL2021 Fiber (ON164651) had 6 glycosylation sites and 107 phosphorylation sites, exerted adhesion receptor-mediated virion attachment to host cell, which was the same as CAdV-2-AC_000020.1 Fiber. The Fiber tertiary structure of the CAdV-1-JL2021 and CAdV-2-AC_000020.1 was different, but they had the same coxsackievirus and adenovirus receptor. “VATTSPTLTFAYPLIKNNNH” were predicted to be the potential CAdV-1 B cell linear epitope. The MHC-I binding peptide “KLGVKPTTY” were both presented in the CAdV-1-JL2021 and CAdV-2-AC_000020.1 Fiber and it is useful to design the canine adenovirus vaccine.